2020
DOI: 10.12659/msm.919565
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Pituitary Adenoma Consistency and Extent of Resection Based on Tumor/Cerebellar Peduncle T2-Weighted Imaging Intensity (TCTI) Ratio of the Point on Preoperative Magnetic Resonance Imaging (MRI) Corresponding to the Residual Point on Postoperative MRI

Abstract: Background:Controversies exist in imaging modalities for predicting adenoma consistency. In this study, we proposed a method of predicting consistency by magnetic resonance T2-sequence imaging based on adenoma to cerebellar peduncle signal (TCTI) ratio. Material/Methods:Between January 2013 and May 2017, 191 consecutive patients with pituitary adenoma diagnosed at our institution were retrospectively studied. The consistency grade for each lesion was assigned. And the TCTI ratio based on preoperative and posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…The current analysis showed that adenoma consistency was associated with the occurrence of postoperative CSF leakage. Most PAs have a soft texture that can easily be resected with curettage and suction [49]. Hard (fibrous) tumors account for approximately 5%-13% of PA and are difficult to separate from critical structures, often requiring removal using sharp dissection or laser techniques [9,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current analysis showed that adenoma consistency was associated with the occurrence of postoperative CSF leakage. Most PAs have a soft texture that can easily be resected with curettage and suction [49]. Hard (fibrous) tumors account for approximately 5%-13% of PA and are difficult to separate from critical structures, often requiring removal using sharp dissection or laser techniques [9,49].…”
Section: Discussionmentioning
confidence: 99%
“…Most PAs have a soft texture that can easily be resected with curettage and suction [49]. Hard (fibrous) tumors account for approximately 5%-13% of PA and are difficult to separate from critical structures, often requiring removal using sharp dissection or laser techniques [9,49]. Therefore, the consistency of an adenoma affects its resection success [50].…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, currently, studies on preoperative prediction of tumor consistency have focused on imaging findings on T2-WI ( 11 , 22 ). Although there are controversies, it seems that T2-WI strongly indicates tumor consistency ( 23 ). Some studies have shown that a low signal on T2-weighted images corresponds to fibrotic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The current analysis showed that adenoma consistency was associated with the occurrence of postoperative CSF leakage. Most PAs have a soft texture that can easily be resected with curettage and suction [49]. Hard ( brous) tumors account for approximately 5-13% of PA and are di cult to separate from critical structures, often requiring removal using sharp dissection or laser techniques [10,49].…”
Section: Discussionmentioning
confidence: 99%
“…Most PAs have a soft texture that can easily be resected with curettage and suction [49]. Hard ( brous) tumors account for approximately 5-13% of PA and are di cult to separate from critical structures, often requiring removal using sharp dissection or laser techniques [10,49]. Therefore, the consistency of an adenoma affects its resection success [50].…”
Section: Discussionmentioning
confidence: 99%